Dissimilar laser welding of a CoCrFeMnNi high entropy alloy to 316 stainless steel. (1st January 2022) - Oliveira, J.P.; Shen, Jiajia; Zeng, Z.; Park, Jeong Min; Choi, Yeon Taek; Schell, N.; Maawad, E.; Zhou, N.; Kim, Hyoung Seop
Abstract: In this work, laser welding of a rolled CoCrFeMnNi high entropy alloy to 316 stainless steel was performed. Defect-free joints were obtained. The microstructure evolution across the welded joints was assessed and rationalized by coupling electron microscopy, high energy synchrotron X-ray diffraction, mechanical property evaluation, and thermodynamic calculations. The fusion zone microstructure was composed of a single FCC phase, and a hardness increase at this location was observed. Such results can be attributed to the formation of a new solid solution (arising from the mixing of the two base materials). Moreover, the incorporation of carbon in the fusion zone upon melting of the stainless steel also aids in the strengthening effect observed. The welded joints presented good mechanical properties, with fracture occurring at the fusion zone. This can be ascribed to the non-favourable, i.e., large grain size, microstructure that developed at this location. Graphical abstract: Image, graphical abstract